2017
DOI: 10.1038/s41598-017-01303-4
|View full text |Cite
|
Sign up to set email alerts
|

Elastic turbulence in entangled semi-dilute DNA solutions measured with optical coherence tomography velocimetry

Abstract: The flow instabilities of solutions of high molecular weight DNA in the entangled semi-dilute concentration regime were investigated using optical coherence tomography velocimetry, a technique that provides high spatial (probe volumes of 3.4 pL) and temporal resolution (sub μs) information on the flow behaviour of complex fluids in a rheometer. The velocity profiles of the opaque DNA solutions (high and low salt) were measured as a function of the distance across the gap of a parallel plate rheometer, and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 67 publications
1
14
0
Order By: Relevance
“…Here, it was found that only high levels of entanglement (Z [214]. Finally, recent methods in optical coherence tomography and velocimetry measurements have further confirmed the existence of shear banded flow profiles in highly entangled DNA solutions [215].…”
Section: Shear Banding In Entangled Dna Solutionssupporting
confidence: 58%
“…Here, it was found that only high levels of entanglement (Z [214]. Finally, recent methods in optical coherence tomography and velocimetry measurements have further confirmed the existence of shear banded flow profiles in highly entangled DNA solutions [215].…”
Section: Shear Banding In Entangled Dna Solutionssupporting
confidence: 58%
“…Furthermore, DOCT appears capable of very accurate measurement of velocity profile very close to a channel wall [18]. Due to the high sampling rate (which varies from tens to some hundreds of kHz), DOCT can be utilized not only on laminar, but also on turbulent flows [19]. When DOCT is combined with pressure loss (e.g., pipe flow) or shear stress (e.g., rotational rheometers) measurements, velocity profiling (i.e., calculation of local viscosities of the studied fluid) becomes possible.…”
Section: Methodsmentioning
confidence: 99%
“…The polymer type, concentration, solvent type and so on are both related to the occurrence of elastic turbulence. Different polymers such as PAM, PEO [18,46], DNA [47]and hydrolyzed PAM (HPAM) [19-21, 36, 48], due to the discrepancy of polymer relaxation time, chain length and molecular weight, have different onset values of elastic turbulence. Not only for polymers, it was found that micelles could induce similar elastic turbulence phenomena under some conditions [49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%